PENENTUAN RISIKO KRITIS PADA DISTRIBUSI GAS DENGAN MENGGUNAKAN INTEGRASI METODE AHP, RISK MANAGEMENT DAN - Julian Yohanes Hamelberg; Agung Sutrisno; Charles Ch Punuhsingon (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2017)
This research using integration of AHP and SWOT within Risk Management is in determining critical risk variables at PT. Perusahaan Gas Negara (Persero)Tbk and proposing then mitigation measure.From the result obtained, the most critical risk variables are technical risk variable with risk weight around 0.441 and rank 3, followed by economic risk with the risk weight 0.209 and rank 2, market risk with the risk weight 0.146 and rank 3 finally political risk with the risk weight 0.106 and rank 4. By using SWOT Analysis, the current position is of the company is at quadrant 1 wich using comparative advantage strategic. Key Word: AHP, Risk Management, SWOT